Rupestrian Habitat: Sustainability and Energy Performance - Lorena Musotto (Agathón)
The article analyses the solutions and the settlement characteristics developed in the Mediterranean area, with reference to the hypogean and rupestrian-dwellings, and investigates the reasons that have led man to prefer forms of subtractive architecture. The critical re-reading of the phenomenon of troglodyteism has brought out features of rock living so far still little investigated; this is due to the lack of studies able to translate the energetic behavior of these constructive solutions to the different climatic and environmental stresses in measurable data.